Scale-up polymeric-based nanoparticles drug delivery systems: Development and challenges - Yedi Herdiana; Nasrul Wathoni; Shaharum Shamsuddin; Muchtaridi Muchtaridi (OpenNano, 2022)
The development of nanotechnology as a crucial technology in recent years has resulted in new and creative nanomedicine applications. The characteristics of nanomedicine are determined by size, surface, drug loading, targeting potential and combination with diagnostic agents for therapeutic applications to form nano multifunctional devices. Nanomedicine provides a new healthcare paradigm and is capable of revitalizing existing clinical products. Polymeric nanoparticles (PNPs) are promising nanomedicines. With increasing demands for medical, pharmaceutical, or nutritional applications, nanoparticles (NPs) require high reproducibility, homogeneity, and control over their properties; upscaling processes are unavoidable. Conventional small-scale laboratory synthesis techniques for PNPs are subject to batch-to-batch variability. Increasing the installation size from laboratory scale to industrial scale presents many difficulties. This review explores recent advances in developing PNPs with high productivity systems for synthesizing NPs in an easy, fast, and controlled manner and their challenges in development, optimization, enhancement, feasibility, and fabrication. There are advantages in the use of biocompatible and biodegradable properties. Upscaling processes occur a lot in metal NPs, which can be a reference in the development of PNPs; there are similar challenges in the development of PNPs.